Perkembangan Kerajinan Sulam Benang Emas di Jambi Kota Seberang Tahun 1980-2016 - Angela Sihaloho, Diana; Itawan , Devi; Risa Mustafa , Hanif (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Gold thread embroidery is a typical Jambi Malay handicraft, which can be done by women in Jambi Kota Seberang. The existence of gold thread embroidery crafts as a hereditary activity and meet the needs of life. This study aims to convey that gold thread embroidery as a cultural heritage from Jambi, the development of gold thread embroidery crafts in Jambi Kota Seberang and the impact of handicrafts on craftsmen and communities in Jambi Kota Seberang. In research using historical research methods consisting of four stages: heuristics, source criticism, interpretation and historiography. The results of this study stated that the craft of gold thread embroidery in the 1980s developed both in terms of human resources, production and marketing. In general, gold thread embroidery crafts are in the form of home industry or businesses in homes. The gold thread embroidery business did not receive support from the Jambi Province Dekranasda, Jambi City Dekranasda and Jambi City Disperindag. In addition, there is an embroidered wage system. Then in 2016, gold thread embroidery crafts began to regress, it can be seen from the level of human resources, production and marketing. In addition, the existence of gold thread embroidery crafts has a social, cultural and economic impact on craftsmen and the people of Jambi Kota Seberang.